DECOLONIZATION AND IDENTITY IN CONTEMPORARY RUSSIAN-LANGUAGE POETRY OF KAZAKHSTAN (2019–2024) - Melnova, Katerina; Guyzel K. Temirgaliyeva; Aigerim A. Gilea (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Objective: This article examines how contemporary Russian-language poetry in Kazakhstan from 2019 to 2024 engages with themes of decolonization and identity. Method: Drawing on a qualitative analysis of works by Kazakhstani Russophone poets, we explore how these writers navigate the legacy of Russian cultural dominance while asserting local and hybrid identities. Through close reading of poetic texts (with original Russian and English translation), we illustrate how these poets both confront and reclaim the Russian language as a medium for Kazakhstani expression. Results: The study finds that recent geopolitical events have intensified reflection on language and identity among Kazakhstani poets. Many poets incorporate bilingual elements, cultural nostalgia, and self-irony in their verses, challenging colonial narratives without entirely rejecting the Russian language. Novelty: The findings contribute to understanding the complex hybrid identity of Russophone literature in post-Soviet Kazakhstan and its role in the ongoing decolonization of the cultural space.